(untitled) (Indian Journal of Arid Horticulture, 2013)
Post-harvest disease management is one of the biggest challenges in intensive fruit production systems. Compare to the vast production of fruits in India, the fruit export from the country has been negligible. A major constraint has been the enormous losses to fruits have been estimated to be in the range of 5-50% or more of the harvest. The fruit-exporting countries have strict requirements to meet health standards. These requirements have adversely affected the fungicide application on harvested fruits. The search for alternative treatments have yielded positive results with homeopathic drugs, hot water treatment, plant growth regulators has proved effective against post harvest diseases of harvested fruits. Applications of Gibberallic acid reduced diseases .